2021
DOI: 10.14746/ssllt.2021.11.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The gender factor in the perception of English segments by non-native speakers

Abstract: The aim of the paper is to present the findings of an empirical study which contributes to the ongoing research into gender effects on second language acquisition by exploring a biological influence on L2 pronunciation learning. One of the most frequent arguments used to vindicate single-sex education is that there are substantial sensory and perceptual differences between males and females which rationalize gender-specific teaching methods and gender-segregation at schools. The present study provides some pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Unlike previous research on language learning and phonetics that showed a gender gap in sound perception (e.g., Hansen Edwards 2008;Moyer 2010Moyer , 2016, the present study indicated that females did not significantly outperform males in the perception task involving auditory discrimination. However, the lack of a significant gender effect in learners' perceptions of Arabic contrastive consonants is in line with some previous research in the field of second-language acquisition (e.g., Bryla-Cruz 2021). This implies that gender may not be a major factor in determining how people perceive and process phonetic information in a second language.…”
Section: Discussionsupporting
confidence: 88%
“…Unlike previous research on language learning and phonetics that showed a gender gap in sound perception (e.g., Hansen Edwards 2008;Moyer 2010Moyer , 2016, the present study indicated that females did not significantly outperform males in the perception task involving auditory discrimination. However, the lack of a significant gender effect in learners' perceptions of Arabic contrastive consonants is in line with some previous research in the field of second-language acquisition (e.g., Bryla-Cruz 2021). This implies that gender may not be a major factor in determining how people perceive and process phonetic information in a second language.…”
Section: Discussionsupporting
confidence: 88%
“…The Gender Role Theory posits that prevalent gender stereotypes are culturally shared expectations for gender appropriate behaviors. Females and males acquire appropriate behaviors and attitudes from the sociocultural environment they grow up in ( Eagly and Karau, 2002 ; Bryła-Cruz, 2021 ). The biological viewpoint suggests that gender difference also depends on cognitive ability and learning style, which are derived from fundamental physiological differences, such as those in the development of the brain or higher-level cortical functions ( de Lima Xavier et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a cornucopia of previous publications that focus on EFL learners' and speakers' problems with /z/ (Broersma 2010;Bryła-Cruz 2021;Demirezen 2016;Flege, Hillenbrand 1986;Lersveen 2018;McAllister 2007;Rugaeseter 2014;Roa et al 2021;Zhang et al 2021). The prior research literature focuses on i) the perception of the /s/ -/z/ contrast by EFL speakers and their English L1 controls (Broersma 2010;Flege, Hillenbrand 1986), ii) the perception of the /s/ -/z/ contrast by EFL speakers without the reference to the English L1 controls (McAllister 2007;Rugaeseter 2014;Roa et al 2021), iii) EFL speakers' perception and production of English fricatives inclusive of /z/ (Demirezen 2016;Lersveen 2018;Zhang et al 2021), and iv) gender differences in the production and perception of /z/ (Bryła-Cruz 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gender differences in the production and perception of English consonants, inclusive of /z/, are explored by Bryła-Cruz (2021). She suggests that the /s/ -/z/ contrast is difficult to Polish L1 EFL speakers in the word-final position.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation